Removal of heavy metals from car wash wastewater by using bentonite clay - Dzulaikha Khairuddin; Siti Nurhidayah Khalid; Muhammad Zulhusni Che Razali (Penerbit Universiti Kebangsaan Malaysia, 2024)
The contamination of water by heavy metals poses significant environmental risks, impacting ecosystems and human well-being. In response, this study investigates methods for eliminating heavy metals from car wash wastewater, focusing on adsorption techniques using the flocculation test. Recent advancements highlight the effectiveness and eco-friendly attributes of natural bentonite and modified bentonite. The primary goal is to assess the capacity of these clays in adsorbing heavy metals without the need for additional chemicals. Our findings demonstrate that modified bentonite holds promise in removing copper and zinc from car wash wastewater, achieving reductions of up to 90%, while iron reduction was around 50% with modified bentonite-zeolite. For iron reduction, raw bentonite alone proved effective, achieving 70% to 80% removal without the combination with zeolite. Additionally, we evaluate the treated water’s suitability for recycling and reuse. While iron, copper, zinc, and pH levels meet recommended standards, other factors like turbidity, color, temperature, and total dissolved solids play critical roles in determining water quality for car wash applications. This study shows that turbidity, color, and total dissolved solids significantly increased due to the natural color of bentonite clay, with no chemical additives used to neutralize the color. Despite these increases, all parameters, except for color, fall within the acceptable range as per the National Water Quality Standard and the Recommended Raw Water Quality Standard. To further enhance the effectiveness of bentonite for heavy metal adsorption and gain deeper insights into its adsorption mechanisms, future research should utilize advanced characterization techniques, such as X-ray diffraction and scanning electron microscopy, to better understand the surface properties and structural changes of bentonite before and after modification, as well as following heavy metal adsorption.